Astyanax ajuricaba: a new species from the Amazon basin in Brazil (Characiformes: Characidae) - Marinho, Manoela M. F. [UNESP]; Lima, Flávio C. T. (Sociedade Brasileira de Ictiologia, 2009)
Uma nova espécie de Astyanax é descrita de diversas localidades nas bacias dos rios Negro, Solimões e baixo Tapajós, bacia Amazônica, Brasil. A nova espécie pode ser distinguida de todos os demais Characidae por um padrão de colorido único, que consiste na combinação da presença de uma linha médio-lateral estreita e escura, uma mácula umeral escura bem desenvolvida e verticalmente alongada e o lobo superior da nadadeira caudal e raios medianos escuros, com uma mancha ocelada clara presente no terço anterior do lobo.

A new Astyanax species is described from several localities in the rio Negro, rio Solimões and lower rio Tapajós basins, Amazon basin, Brazil. The new species is distinguished from all remaining characids by its unique color pattern consisting of the combination of presence of a conspicuous, narrow dark midlateral stripe, a well-developed vertically-elongated dark humeral spot, and upper caudal-fin lobe and middle caudal-fin rays dark, with a rounded clear ocellated spot present at anterior third of caudal-fin lobe.
Keywords: Rio Negro; Rio Tapajós; Moenkhausia lepidura species-group; Caudal-fin ocellated spot